Introduction to political science - Moten, Abdul Rashid; Syed Serajul Islam (Cencage Learning, 2020)
This is a unique book, in that it combines Western and Islamic perspectives on some of the key concepts and issues in Political Science. It is easy to read and answers most questions regarding political theories, comparative politics, public administration and international relations. It contains a total of 28 chapters covering almost all the topics considered essential for students of political science in the 21st century. It also defines frequently used Islamic and Western terms that are important for political analysis and comprehension. Anyone remotely interested in the field of political science and political philosophy would find this book to be a priceless addition to their personal collection.